Increased platelet deposition on atherosclerotic coronary arteries. - van Zanten, G H (1994)
A ruptured atherosclerotic plaque leads to exposure of deeper layers of the plaque to flowing blood and subsequently to thrombus formation. In contrast to the wealth of data on the occurrence of thrombi, little is known about the reasons why an atherosclerotic plaque is thrombogenic. One of the reasons is the relative inaccessibility of the atherosclerotic plaque. We have circumvented this problem by using 6-microns cryostat cross sections of human coronary arteries. These sections were mounted on coverslips that were exposed to flowing blood in a rectangular perfusion chamber. In normal-appearing arteries, platelet deposition was seen on the luminal side of the intima and on the adventitia. In atherosclerotic arteries, strongly increased platelet deposition was seen on the connective tissue of specific parts of the atherosclerotic plaque. The central lipid core of an advanced plaque was not reactive towards platelets. The results indicate that the atherosclerotic plaque by itself is more thrombogenic than the normal vessel wall. To study the cause of the increased thrombus formation on the atherosclerotic plaque, perfusion studies were combined with immunohistochemical studies. Immunohistochemical studies of adhesive proteins showed enrichment of collagen types I, III, V, and VI, vitronectin, fibronectin, fibrinogen/fibrin, and thrombospondin in the atherosclerotic plaque. Laminin and collagen type IV were not enriched. von Willebrand Factor (vWF) was not present in the plaque. The pattern of increased platelet deposition in serial cross sections corresponded best with areas in which collagen types I and III were enriched, but there were also areas in the plaque where both collagens were enriched but no increased reactivity was seen. Inhibition of platelet adhesion with a large range of antibodies or specific inhibitors showed that vWF from plasma and collagen types I and/or III in the plaque were involved. Fibronectin from plasma and fibronectin, fibrinogen, laminin, and thrombospondin in the vessel wall had no effect on platelet adhesion. We conclude that the increased thrombogenicity of atherosclerotic lesions is due to changes in quantity and nature of collagen types I and/or III.